EURASIAN CONTINENTAL INTEGRATION: PREREQUISITES AND DIFFICULTIES - BEZRUKOV, Leonid (CENTRAL ASIA AND THE CAUCASUS, 2019)
This study seeks to address underexplored issues in Eurasian continental integration, such as the impact of the continental (landlocked) location of vast inland territories on their economic development and possible ways to overcome transportation-economic difficulties within the framework of a Greater Eurasia. It notes the trend towards the progressive formation of this broad integration grouping on a continental scale and, based on a politico-economic understanding of the essence of the new bloc, determines its current composition, which mainly includes member countries of the Eurasian Economic Union and member and observer countries of the Shanghai Cooperation Organization. The author considers the conceptual views of geopoliticians and geographers on the role and place of continental Eurasia in the world and examines the main prerequisites and difficulties of Eurasian continental integration. The study reveals a common geographical feature of the countries included in Greater Eurasia: the unique ultra-continental position of their inland regions, located, globally speaking, at the greatest distance from economical sea routes and major world markets. A case study of the Central Asian countries, Russia’s Siberia, and the western regions of China shows the negative impact of the ultra-continentality factor as manifested in increased transport costs, which creates serious barriers to economic growth and foreign trade activity. It is suggested that accelerated creation of latitudinal and meridional international transport corridors is a promising way to achieve greater economic consolidation of the inland regions of Greater Eurasia. The study highlights the new opportunities for the economic development of Russia’s ultra-continental macro-regions offered by Eurasian continental integration.